2011
DOI: 10.3109/01942638.2011.572150
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Assessment in Children with Cerebral Palsy: A Clinimetric Review

Abstract: This review evaluates the clinimetric properties of tactile assessments for children with cerebral palsy. Assessment of registration was reported using Semmes Weinstein Monofilaments (SWMs) or exteroception. Assessment of two-point discrimination was reported using the Disk-Criminator R or paperclip methods; Single point localization and double simultaneous were reported from the Neurosensory Motor Developmental Assessment (NSMDA); graphaesthesia was reported from the Sensory Integration and Praxis Test (SIPT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 63 publications
0
73
0
Order By: Relevance
“…In contrast to previous reviews [9,20,23,30,31,41], this study covers a broad paediatric age range and multiple neurological conditions. Recommendations for a clinimetrically-sound neurological test require a standardised test protocol with population-specific evidence, as clinimetric properties from other populations are not inherently transferable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous reviews [9,20,23,30,31,41], this study covers a broad paediatric age range and multiple neurological conditions. Recommendations for a clinimetrically-sound neurological test require a standardised test protocol with population-specific evidence, as clinimetric properties from other populations are not inherently transferable.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Other systematic reviews have identified the lack of high quality clinimetric evidence for upper limb tests in children and young people with a neurological condition. [1,9] The clinimetric evidence for other lower limb neurological impairment tests for children and young people with cerebral palsy and other neurological conditions remains unknown. Therefore, the aims of this study were to:…”
Section: Introductionmentioning
confidence: 99%
“…We also excluded other tactile assessment tools designed for specific populations (36) and electroencephalography (EEG), which is used to diagnose SPDs (108). In addition, we excluded other instruments that are commercially available but for which scientific studies have not consulted databases on the psychometric properties of the tests employed or, in some cases, for which no standardized methods are provided for assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, Auld et al review different clinically useful tools for the assessment of tactile SI, especially for evaluating registration and perception (36). In addition, it could be interesting to develop new assessments of pain for children.…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 99%
“…Movement of an object across the skin by an examiner has been found to achieve success equivalent to a child performing the exploration themselves (Cermak, ). Recent studies have recommended removing the need for in‐hand manipulation when testing children who cannot move the object themselves (Auld et al .). This supports our use of standardised motor‐assisted haptic exploration as a strategy to compensate for the neurological and/or musculoskeletal impairments experienced by children with CP that may restrict in‐hand manipulation and expected exploratory procedures.…”
Section: Discussionmentioning
confidence: 99%